Les péripéties cynégétiques des Noirs d’Équateur. De l’art de rester humain et chrétien tout en chassant - Armelle Lorcy (Journal de la Société des Américanistes)
Ecuadorian Blacks and their vicissitudes in the forest. On the art of staying human and Christian while hunting. Looking at hunting offers an interesting angle to study how the Blacks of the Pacific Lowlands of Ecuador conceive of their « humanity ». During trips in the forest it often happens that hunters are confronted with various kinds of non human beings such as the tunda. Sometimes they have repeatedly bad luck or, as they express it themselves, « a damaged arm ». To avoid such mishaps, the Blacks of the Rio Cayapas area take various measures to prevent that their human status « drifts » into that of an animal or an enemy. What it means to be a human person cannot be understood apart from ideas about the divine. Hunting and the precautions hunters take reveal the importance of the forest (el monte) as a symbolic space. It also reveals the crucial role of Christianity, even in situations which are not usually considered « religious ». Finally, conceptions about the realm of the non-human and ideas concerning metamorphosis are compared to Amerindian practices.